Clothing the New World Church : liturgical textiles of Spanish America, 1520-1820 - Stanfield-Mazzi, Maya Selama, 1972- (University of Notre Dame Press, 2021)
Clothing the New World Church makes a significant contribution to the fields of textile studies, art history, Church history, and Latin American studies, and to interdisciplinary scholarship on material culture and indigenous agency in the New World.